Lithium-assisted proton conduction at 150 degrees C in a microporous triazine-phenol polymer - Nandi, Shyamapada; Dhavale, Vishal M.; Shalini, Sorout; Werner-Zwanziger, Ulrike; Singh, Harpreet; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Materials Interfaces, 2015)
Keywords: conduction; hydrophobic polar frameworks; lithiated polymers; proton conduction; triazine-phenol polymers

Pd loaded amphiphilic COF as catalyst for multi-fold Heck reactions, C-C couplings and CO oxidation - Mullangi, Dinesh; Nandi, Shyamapada; Shalini, Sorout; Sreedhala, Sheshadri; Vinod, Chathakudath P.; Vaidhyanathan, Ramanathan (Scientific Reports, 2015)
COFs represent a class of polymers with designable crystalline structures capable of interacting with active metal nanoparticles to form excellent heterogeneous catalysts. Many valuable ligands/monomers employed in making coordination/organic polymers are prepared via Heck and C-C couplings. Here, we report an amphiphilic triazine COF and the facile single-step loading of Pd-0 nanoparticles into it. An 18-20% nano-Pd loading gives highly active composite working in open air at low concentrations (Conc. Pd(0) < 0.05 mol%, average TON 1500) catalyzing simultaneous multiple site Heck couplings and C-C couplings using `non-boronic acid' substrates, and exhibits good recyclability with no sign of catalyst leaching. As an oxidation catalyst, it shows 100% conversion of CO to CO2 at 150 degrees C with no loss of activity with time and between cycles. Both vapor sorptions and contact angle measurements confirm the amphiphilic character of the COF. DFT-TB studies showed the presence of Pd-triazine and Pd-Schiff bond interactions as being favorable.

10000-Fold enhancement in proton conduction by doping of cesium ions in a proton-conducting zwitterionic metal-organic framework - Shalini, Sorout; Aggarwal, Shubhangi; Singh, Santosh K.; Dutt, Malvika; Ajithkumar, Thallaseril G.; Vaidhyanathan, Ramanathan (European Journal of Inorganic Chemistry, 2016)
Developing metal-organic framework (MOF)-based proton-conducting electrolytes for fuel-cell applications is an important target that has drawn a lot of attention. A key approach involves the selective replacement of the guest species within the pores to enhance performance. The modular and crystalline nature of the MOF permits controlled introduction of such species and characterization of their compositions with high precision, a task which is very difficult to achieve in amorphous polymers. Herein, we partially replaced the protons of a zwitterionic pyridinol in Mg(terephthalate)(pyridinol) MOF 1 with Cs+ ions, which brought about a 10000-fold increase in the proton conductivity (10(-6) to 10(-2) S cm(-1)). Interestingly, Li+ ions could not be loaded, whereas Cs+ ions with smaller hydrated ionic radii could be loaded, and the loading was controlled as a function of time. The Cs+ loading nearly halved the activation energy (from 0.35 for 1 to 0.19 eV for _Cs). The highest conductivities were realized for an optimal loading of Cs+ ions, which was found to be about 10 % in this case.

1000-fold enhancement in proton conductivity of a MOF using post-synthetically anchored proton transporters - Shalini, Sorout; Dhavale, Vishal M.; Eldho, Kavalakal Mathai; Kurungot, Sreekumar; Ajithkumar, Thalasseril G.; Vaidhyanathan, Ramanathan (Scientific Reports, 2016)
Pyridinol, a coordinating zwitter-ionic species serves as stoichiometrically loadable and non-leachable proton carrier. The partial replacement of the pyridinol by stronger hydrogen bonding, coordinating guest, ethylene glycol (EG), offers 1000-fold enhancement in conductivity (10(-6) to 10(-3) Scm(-1)) with record low activation energy (0.11 eV). Atomic modeling coupled with C-13-SSNMR provides insights into the potential proton conduction pathway functionalized with post-synthetically anchored dynamic proton transporting EG moieties.

Low-overpotential electrocatalytic water splitting with noble-metal-free nanoparticles supported in a sp(3) n-rich flexible COF - Mullangi, Dinesh; Dhavale, Vishal M.; Shalini, Sorout; Nandi, Shyamapada; Collins, Sean; Woo, Tom; Kurungot, Sreekumar; Vaidhyanathan, Ramanathan (Advanced Energy Materials, 2016)
Covalent organic frameworks (COFs) are crystalline organic polymers with tunable structures. Here, a COF is prepared using building units with highly flexible tetrahedral sp(3) nitrogens. This flexibility gives rise to structural changes which generate mesopores capable of confining very small (<2 nm sized) non-noble-metal-based nanoparticles (NPs). This nanocomposite shows exceptional activity toward the oxygen-evolution reaction from alkaline water with an overpotential of 258 mV at a current density of 10 mA cm(-2). The overpotential observed in the COF-nanoparticle system is the best in class, and is close to the current record of approximate to 200 mV for any noble-metalfree electrocatalytic water splitting system-the Fe-Co-Ni metal-oxide-film system. Also, it possesses outstanding kinetics (Tafel slope of 38.9 mV dec(-1)) for the reaction. The COF is able to stabilize such small-sized NP in the absence of any capping agent because of the COF-Ni(OH)(2) interactions arising from the N-rich backbone of the COF. Density-functional-theory modeling of the interaction between the hexagonal Ni(OH)(2) nanosheets and the COF shows that in the most favorable configuration the Ni(OH)(2) nanosheets are sandwiched between the sp(3) nitrogens of the adjacent COF layers and this can be crucial to maximizing their synergistic interactions.